A Bipedal DNA Brownian Motor with Coordinated Legs - Omabegho, Tosan (2009)
A significant challenge in engineering molecular motors is designing mechanisms to coordinate the motion between multiple domains of the motor so as to bias random motion. For bipedal motors, this challenge takes the form of coordinating the movement of the biped’s legs, so they can move in a synchronized fashion. To address this problem, we have constructed an autonomous DNA bipedal nanorobot that coordinates the action of its two legs by coupling room temperature thermal energy with the catalysis of metastable DNA fuel strand hybrids. This coupling leads to a chemically ratcheted unidirectional walk along a DNA track. By crosslinking aliquots of the walker covalently to its track in successive walking states, we demonstrate that the walker can complete a full walking cycle on a track whose length could be extended for longer walks.